2018
DOI: 10.1108/jfmpc-06-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Competencies expected of graduate quantity surveyors working in developing countries

Abstract: Purpose Quantity surveying education in Sri Lanka (SL) presently does not appear to be catering to the industry needs indicating that it may not be up to the expected standard. Hence, the purpose of this study is to identify the gap between the competencies of graduate quantity surveyors (QSs) and the competencies that industry in SL expects from them. Design/methodology/approach A hybrid approach was used, consisting of desk reviews, expert interviews and a questionnaire survey. A comparative analysis ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 9 publications
0
61
0
1
Order By: Relevance
“…Built environment graduates, particularly the quantity surveyors of the future, will need to be highly technical, adaptable, good communicators and also lifelong learners undertaking continuing professional development (CPD). This is the view of many proponents in this field, including Nkado and Meyer (2001), Male (1990), Yogeshwaran et al (2018), Shafie et al (2014) and Perera et al (2013). Such a goal provides the modern academic with many challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Built environment graduates, particularly the quantity surveyors of the future, will need to be highly technical, adaptable, good communicators and also lifelong learners undertaking continuing professional development (CPD). This is the view of many proponents in this field, including Nkado and Meyer (2001), Male (1990), Yogeshwaran et al (2018), Shafie et al (2014) and Perera et al (2013). Such a goal provides the modern academic with many challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of the study are then presented and discussed before the paper culminates with a conclusion section. Yogeshwaran (2018) highlighted that employers are expecting graduates to become competent professionals at university, via attaining practical knowledge. However, it was found that universities favour providing students with technical knowledge over practical knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification is the capability of QSs to define and measure construction works to value work and control costs at all stages of the construction process (RICS, 2018). An understanding of the rules and various categories of measurement is needed to quantify construction work in the production of pricing documents (Yogeshwaran et al, 2018). Dada and Jagboro's (2012) This author accepted manuscript is deposited under a Creative Commons Attribution Non-commercial 4.0 International (CC BY-NC) licence.…”
Section: The Situation Nowmentioning
confidence: 99%
“…presentation skills, and client care (Yogeshwaran et al, 2018). In this vein, business management plays a vital role in organising, analysing and planning various types of business operations in order to attain objectives and justify the existence of the organisation (Oosthuizen and Berry, 2013).…”
Section: The Situation Nowmentioning
confidence: 99%
See 1 more Smart Citation